Protective Effects of Lentinan Against Lipopolysaccharide-Induced Mastitis in Mice - Yin, Huifang; Xue, Guanhong; Dai, Ailing; Wu, Haichong (Frontiers in Pharmacology, 2021)
Mastitis is a worldwide production disease in dairy cows, which mainly affects milk yield, causing huge economic losses to dairy farmers. Lentinan is a kind of polysaccharide extracted from Lentinus edodes, which has no toxic and possesses various pharmacological activities including antibacterial and immunomodulatory effects. Therefore, the anti-inflammatory function of lentinan on LPS-stimulated mastitis was carried out, and explored the mechanism involved. In vivo, lentinan greatly reduced LPS stimulated pathological injury, myeloperoxidase (MPO) activity, and the proinflammatory factors production (TNF-α, IL-1β) in mice. Further study was performed to determine the activation of Wnt/β-catenin pathway during LPS stimulation. These results suggested that LPS-induced the activation of Wnt/β-catenin pathway was suppressed by lentinan administration. In vitro, we observed that the mouse mammary epithelial cells (mMECs) viability was not affected by lentinan treatment. As expected, LPS increased the TNF-α, IL-1β protein secretion, and the activation of Wnt/β-catenin pathway that were inhibited by lentinan administration in a dose-dependent manner in mMECs. Conclusively, lentinan exerts anti-inflammatory function in LPS stimulated mastitis via inhibiting the activation of Wnt/β-catenin pathway. Thus, the results of our study also gave an insight that lentinan may serve as a potential treatment for mastitis.